2012
DOI: 10.1371/journal.pone.0045334
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Long-Term Variations in an Elephant Piosphere Effect to Manage Impacts

Abstract: Surface water availability is a key driver of elephant impacts on biological diversity. Thus, understanding the spatio-temporal variations of these impacts in relation to water is critical to their management. However, elephant piosphere effects (i.e. the radial pattern of attenuating impact) are poorly described, with few long-term quantitative studies. Our understanding is further confounded by the complexity of systems with elephant (i.e. fenced, multiple water points, seasonal water availability, varying p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 36 publications
3
71
0
Order By: Relevance
“…Piospheric studies on species composition, richness, and diversity indices have been done in most parts of the world including Australia (Landman et al 2012), Asia (Shahriary et al 2012), Southern Africa (Todd 2006), Northern Africa (Tarhouni et al 2007), and Uganda (Egeru 2014;Egeru et al 2015). Nevertheless, there have been no studies conducted in Kenya, especially in the southern rangelands where water interventions have been widely undertaken to alleviate water shortage and enhance pastoral livelihoods (Opiyo et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Piospheric studies on species composition, richness, and diversity indices have been done in most parts of the world including Australia (Landman et al 2012), Asia (Shahriary et al 2012), Southern Africa (Todd 2006), Northern Africa (Tarhouni et al 2007), and Uganda (Egeru 2014;Egeru et al 2015). Nevertheless, there have been no studies conducted in Kenya, especially in the southern rangelands where water interventions have been widely undertaken to alleviate water shortage and enhance pastoral livelihoods (Opiyo et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of any one of these resources at any given location in a semi-arid landscape will determine the level of herbivore influence on vegetation dynamics at both spatial and temporal scales (Yu and Wu 2010;Wesuls et al 2013). The intensity of herbivore influence is dependent on the spatio-temporal patterns of foraging decisions (Landman et al 2012). Proximity to water, topography and the availability of food have been identified as key determinants of foraging decisions at landscape level (Bailey and Provenza 2008;Ash et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Proximity to water, topography and the availability of food have been identified as key determinants of foraging decisions at landscape level (Bailey and Provenza 2008;Ash et al 2004). These foraging decisions have impacts on biological diversity because herbivore foraging affects various aspects of vegetation dynamics (Landman et al 2012). Further, adaptive components such as deferred resting of grazing sites to protect forage plants during critical life stages are important in influencing vegetation dynamics (Linstädter et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed that piospheres, created to curb water scarcity in most rangelands across the world, have adverse effects on both soil and vegetation (Brooks and Matchett 2006;Landman et al 2012;Shahriary et al 2012).…”
Section: Introductionmentioning
confidence: 99%